The effect of foreign accent on employability: a study of the aural dimensions of aesthetic labour in customer-facing and non-customer-facing jobs. (June 2017) - Timming, Andrew R
Using quantitative methods, this article examines the effect of foreign accents on job applicants' employability ratings in the context of a simulated employment interview experiment conducted in the USA. It builds upon the literature on aesthetic labour, which focuses largely on the role of physical appearance in employment relations, by shifting attention to its under-investigated auditory and aural dimensions. The results suggest that the managerial respondents actively discriminate in telephone-based job interviews against applicants speaking Chinese-, Mexican- and Indian-accented English, and all three are rated higher in non-customer-facing jobs than in customer-facing jobs. Job applicants who speak British-accented English, especially men, fare as well as, and at times better than, native candidates who speak American English. The article makes a contribution to the sociological literatures surrounding aesthetic labour and discrimination and prejudice against migrant workers.